Parkinson's Disease-Related Risk of Suicide and Effect of Deep Brain Stimulation: Meta-Analysis - Du, Juncong (Parkinsons Dis, 2020)
BACKGROUND: Previous studies investigated the risk of suicide in patients with Parkinson's disease (PD) but reported discrepant results. Deep brain stimulation (DBS) is an effective therapy for PD, while its effect on suicide risk has seldom been researched. This meta-analysis aimed to estimate the risk of suicide and/or suicidal ideation in PD patients and in PD patients who underwent DBS. METHODS: Relevant articles published in the PubMed or EMBASE or CNKI database from 1990 to December 2019 were sourced, and the combined standardized mortality rate (SMR) or odds ratio (OR) was pooled. RESULT: A total of 1070 articles were found. After screening, 4 cross-sectional studies, 4 cohort studies, 2 randomized controlled trial studies, and 2 case-control studies were included in this meta-analysis. Pooled data indicated that PD patients may have increased risk of suicide (lnSMR, 0.459; 95% confidence interval (CI), 0.286 to 0.632; p < 0.001). No significant difference was found in the risk of suicide when comparing PD patients who underwent DBS with PD patients who received only drug therapy (OR = 2.844, 95%CI: 0.619 to 13.072, p=0.179). DBS may increase the risk of suicide and/or suicidal ideation in PD patients compared with general population (lnSMR = 3.383, 95%CI: 2.839 to 3.927, p < 0.001). CONCLUSION: PD patients have higher risk of suicide and/or suicidal ideation compared with controls, while PD patients who received DBS tend to have an increased risk of suicide or suicidal ideation. Psychological evaluation is needed in PD patients, and pre- and post-operation evaluations are necessary for PD patients who underwent DBS.